Copper coordination polymers constructed from thiazole-5-carboxylic acid: Synthesis, crystal structures, and structural transformation - Natthaya Meundaeng (2018)
© 2016 Elsevier Inc. We have successfully prepared crystals of thiazole-5-carboxylic acid (5-Htza) (L) and three new thiazole-5-carboxylate-based Cu 2+ coordination polymers with different dimensionality, namely, 1D [Cu 2 (5-tza) 2 (1,10-phenanthroline) 2 (NO 3 ) 2 ] (1), 2D [Cu(5-tza) 2 (MeOH) 2 ] (2), and 3D [Cu(5-tza) 2 ]·H 2 O (3). These have been characterized by single crystal X-ray diffraction and thermogravimetry. Interestingly, the 2D network structure of 2 can directly transform into the 3D framework of 3 upon removal of methanol molecules at room temperature. 2 can also undergo structural transformation to produce the same 2D network present in the known [Cu(5-tza) 2 ]·1.5H 2 O upon heat treatment for 2 h. This 2D network can adsorb water and convert to 3 upon exposure to air.